Smart Eco-Tourism Mangroves: A Strategy For Revitalizing Coastal Tourism Areas Based On Green Architecture and Information Technology (Community Service Study in the Belawan Mangrove Ecotourism Area, Medan City) - Bhakti Alamsyah; Jusra Tampubolon; Jufri Antoni; Anita Christine Sembiring; Emmiya Ellovani Br Tarigan; Yovita Simangunsong (International Journal Of Community Service, 2026)
The Belawan mangrove area in Medan City, Indonesia, possesses significant ecotourism potential yet remains underdeveloped due to inadequate physical infrastructure misaligned with green architecture principles and the minimal utilization of information technology for promotion and visitor management. This community service project aimed to revitalize the area through an integrated "smart eco-tourism" strategy combining sustainable facility design with digital marketing and technology-based visitor interpretation. Using a participatory action research approach involving 30 local management group members, the project implemented three main interventions: (1) collaborative green facility planning (elevated boardwalks, natural ventilation, and local eco-friendly materials), (2) digital promotion training (social media management, photography, and QR-code-based interpretive signage), and (3) institutional strengthening. Results showed significant improvements: participants' technical knowledge increased from a mean pre-test score of 54.2 to 81.6 (a 50.6% increase), social media engagement rose by 65%, and visitor numbers grew by 41.8% within three months post-intervention. The successful integration of green architecture and digital tools created a replicable, community-owned model that enhances ecological sustainability while providing tangible economic benefits. This smart eco-tourism framework offers practical guidance for revitalizing similar coastal mangrove destinations across North Sumatra and other developing coastal regions.